The municipal cemetery of Soacha, Cundinamarca: an example of a heritage site that is the scene of tensions - Rivas Estrada, Sebastián (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The study of burial practices expressed over time in the same territory allows them to be approached from a heritage perspective, where the tensions generated by the behaviors of different groups in the face of death activate processes of valuation and appropriation of a space that synthesizes, as few others, the historical memory, religious beliefs and social transformations of the population of Soacha (Cundinamarca). The municipal cemetery of Soacha, besides being the scene of tensions, allows exploring the new manifestations around death and the long indigenous tradition of this territory, occupied since ancient times without interruption for more than 10,000 years. The historical journey, therefore, allows to carry out reflections from the cultural heritage and memory of a territory.